Euribor, Eonia und exteuroSTR: Weichenstellungen der Working Group on Euro Risk-free Rates - Oliver Read; Jochen Beißer (RheinMain University of Applied Sciences, Wiesbaden Institute of Finance and Insurance (wifi), 2019)
Infolge der Anwendung der Benchmark-Verordnung steht fest, dass Eonia und Euribor in der aktuellen Form ab 1. Januar 2020 für Neugeschäft nicht mehr verwendet werden können. Die Working Group on Euro Risk-Free Rates hat Weichen gestellt, um die Lücken zu schließen. Als risikoloser Overnight-Referenzinssatz wurde der exteuroSTR empfohlen. Die EZB startet mit der Veröffentlichung am 2. Oktober 2019. An der Euribor-Nachfolge wird zweigleisig gearbeitet. Einerseits strebt der Administrator European Money Markets Institute eine Zulassung des reformierten Euribor nach der hybriden Ermittlungsmethode an. Ein Antrag wird bei der belgischen Aufsichtsbehörde FSMA bis Juni 2019 gestellt. Andererseits befasst sich die Working Group mit der Entwicklung einer Zinsstruktur auf der Basis des exteuroSTR als Fallback-Lösung für Euribor. – – With the application of the Benchmark Regulation it is clear that Eonia and Euribor cannot be used in the current specification for new business from 1 January 2020. The Working Group on Euro Risk-Free Rates has made decisions to close the gap. It recommended exteuroSTR as risk-free overnight reference rate. The ECB will begin publication on 2 October 2019. The succession of Euribor is being dealt with on a dual track. On one side, the administrator European Money Markets Institute is looking for an approval of the reformed Euribor based on a hybrid methodology. It will file an application with the Belgian regulator FSMA until June 2019. On the other hand, the Working Group is developing a term structure of interest rates on the basis of exteuroSTR as fallback solution for Euribor.
Keywords: E43; G15; G18; 340; Financial benchmarks; Reference rates; ESTER; Eonia; Euribor; Libor; Benchmark Regulation; Working Group on Euro Risk-Free Rates